Aksi Kolaborasi Peningkatan Literasi Numerasi dengan Variasi Metode Pembelajaran dan Adaptasi Teknologi - Sabillah, Izzah; Asyifa, Fatimah Nur; Fatimah, Hervina Rahmawati; Firdaus, Tiara; Sari, Rafika (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The Community Service Program (PkM) at SMPN Satu Atap Cibarusah, Bekasi Regency, aims to enhance the quality of education and student skills through various initiatives, including graphic design training using Canva, library revitalization, the introduction of Shibori batik art, and the implementation of innovative learning methods in Islamic Religious Education (PAI) through the Team Games Tournament (TGT) approach. The Canva training equips students with digital design skills, while library revitalization seeks to increase reading interest through improved facilities and library administration systems. The Shibori batik program not only introduces students to traditional textile art but also instills Pancasila values through creativity and collaboration. The TGT learning method in PAI is applied to enhance students' understanding of halal and haram food and beverages through a cooperative and engaging approach. The results of this program show significant improvements in students' digital skills, literacy, creativity, and comprehension of learning materials. This initiative also encourages active participation and student motivation, positively impacting their educational experience. The success of this program highlights the importance of innovative and participatory approaches in improving the quality of learning in schools.